Dyspnea with anemia turned out to be a case of hereditary hemorrhagic telangiectasia - Sengupta, Amitabha (Medknow Publications & Media Pvt Ltd, 2013)
Hereditary hemorrhagic telangiectasia (HHT) is a rare autosomal dominant inherited disorder of the vascular system. It can be asymptomatic but when symptomatic most common presentation being epistaxis. It can involve any organs of the body like lungs, skin, liver brain, GI mucosa etc. We are reporting a case of HHT presented to us with dyspnea and severe anemia. He had arteriovenous malformations of different visceral organs and telangiectasia of skin along with presence of similar history in first-degree relatives.